2016
DOI: 10.1186/s13287-016-0276-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of immunomodulation by macrophage subsets on osteogenesis in vitro

Abstract: BackgroundBone formation and remodeling are influenced by the inflammatory state of the local microenvironment. In this regard, macrophages are postulated to play a crucial role in modulating osteogenesis. However, the differential effects of macrophage subsets and their plasticity on bone formation are currently unknown.MethodsPolarized primary murine macrophages and preosteoblastic MC3T3 cells were co-cultured to investigate the effect of non-activated M0, pro-inflammatory M1, and tissue-regenerative M2 macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
223
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(248 citation statements)
references
References 38 publications
11
223
1
Order By: Relevance
“…These findings suggest that aged MΦ remain in a preactivated resting state that enhances their responsiveness to exposure of pro-inflammatory stimuli [29]. Loi et al [30] have shown that modulation of macrophage phenotype from M1 to M2 enhances osteogenic ability of MC3T3 cells in an in vitro coculture model. The present study showed that the majority of the aged M0s are both iNOS+ and CD206+.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that aged MΦ remain in a preactivated resting state that enhances their responsiveness to exposure of pro-inflammatory stimuli [29]. Loi et al [30] have shown that modulation of macrophage phenotype from M1 to M2 enhances osteogenic ability of MC3T3 cells in an in vitro coculture model. The present study showed that the majority of the aged M0s are both iNOS+ and CD206+.…”
Section: Discussionmentioning
confidence: 99%
“…Bone fracture is the latent threat associated with osteoporosis [24,25]. The first stage of healing after fracture is inflammation, which leads to granulation tissue formation and disrupts the balance between bone loss and formation [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for this is that during the early stages of bone healing, which is characterized by an acute inflammatory phase, the M1 macrophages act as a key factor in the differentiation of osteoblasts, whereas M2 macrophages take part in the later stage of osteogenesis by inducing the maturation and terminal mineralization of osteoblasts. The transition from the M1 to M2 phenotype is, therefore, considered to be crucial aspect of bone healing and de novo bone formation (Loi, et al, 2016). In the preceding chapter, it was found that the macrophages were capable of inducing the SPHK1 activity in the co-cultured BMSCs, thereby promoting the S1P production.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the conversion of M1 to M2 macrophages significantly improves mineralization in the co-culture system (Loi et al, 2016 MSCs to the injury site and induce bone formation (Takayanagi, 2007). The two major players in bone remodelling -osteoclasts and osteoblasts are coupled through the RANKL-RANK-OPG axis, that osteoblastsderived RANKL combines with its ligand RANK in osteoclasts and plays an indispensable role in osteoclastogenesis; OPG (which is also derived from osteoblasts) reduces osteoclastogenesis by impairing the RANKL-RANK signalling.…”
Section: Regulations Of the Immune System On Bone Remodelingmentioning
confidence: 99%
See 1 more Smart Citation